1974
DOI: 10.1042/bj1440253
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 3′:5′-cyclic monophosphate in young and senescent human fibroblasts during growth and stationary phase in vitro. Effects of prostaglandin E1 and of adrenaline

Abstract: Cyclic AMP levels per mg of cell protein were higher in late-passage (senescent) fibroblasts than in early-passage (young) fibroblasts both during growth and stationary phase, but, because the protein concentration per unit volume in senescent cells was lower than in young cells, the molar concentrations of intracellular cyclic AMP were very similar in the two cell types. In both young and senescent fibroblasts cyclic AMP levels declined during growth and no increase in intracellular cyclic AMP occurred in ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

1975
1975
1988
1988

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…Thus, if donor fibroblasts preserve their typical pattern of 8-receptors throughout the period of cultivation, the age of donor fibroblasts could possibly influence adrenergic responsiveness of cultured cells. Cultured fibroblasts appear to be more sensitive to catecholamines with increasing number of passages (14). Therefore in this study all fibroblast strains were from donors of about the same age and were used within the same passage number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, if donor fibroblasts preserve their typical pattern of 8-receptors throughout the period of cultivation, the age of donor fibroblasts could possibly influence adrenergic responsiveness of cultured cells. Cultured fibroblasts appear to be more sensitive to catecholamines with increasing number of passages (14). Therefore in this study all fibroblast strains were from donors of about the same age and were used within the same passage number.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult, however, to compare the results of the different studies since many factors can modify the cyclic nucleotide synthesis in cultured cells. Culture conditions such as passage number (14), cell density ( 1 6 ) , time after subculture (20), serum concentration (19) and stage of the cell cycle (25) have been shown to influence signiEicantly the response of the cAMP system. We therefore reinvestigated CAMP response to 0-adrenergic stimuli in cultured fibroblasts from CFpatients and from normal controls using strictly defined culture conditions and examined the contribution of the conditioned culture medium to this system.…”
mentioning
confidence: 99%
“…Cell number increased for about 5 days aAer subculture in all conditions tested and then remained stable; doubling time (24 to 36 hr) was the same in all conditions tested. Also, hormone-responsiveness of cAMP content has been shown to vary with time after subculture (16,20). In these experiments (Fig.…”
Section: Growth Of Fibroblasts Related To Changes In Hormone-stimulatmentioning
confidence: 70%
“…Cultured fibroblasts are endowed with the abnormal genetic material yet are remote from the influences of drugs and illness to which the patient is subject, and the biochemical milieu of the fibroblast can be manipulated to a far greater extent than the intact human organism. Fibroblasts possess an adrenergic-responsive adenylate cyclase (EC 4.6.1.1) system (16,20), and the direction of the adenylate cyclase response to isoproterenol in skin fibroblasts from normal and cystic fibrosis (CF) donors has been controversial in the literature. Buchwald (4) first reported that C F fibroblasts produced more cyclic adenosine 3'5'-monophosphate (CAMP) in response to isoproterenol than normal fibroblasts.…”
Section: Speculationmentioning
confidence: 99%
See 1 more Smart Citation